2020
DOI: 10.1111/jonm.12989
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for controlling violence against health care workers: Application of fuzzy analytical hierarchy process and fuzzy additive ratio assessment

Abstract: Objective The present study aimed to identify and prioritize control measures of violence against health care workers (HWs) using the fuzzy analytical hierarchy process (FAHP) and fuzzy additive ratio assessment (ARAS‐F). Background Occupational violence is a pervasive problem in health care centres. Reducing violence against staff is one of the challenges for health care managers. Method At the first stage, the most common criteria and control options for violence against HWs were identified and extracted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
16
0
4
Order By: Relevance
“…Manter o senso de humor e até confrontar o agressor são mecanismos individuais que também aparecem nos estudos (Abraham, 2018;Dadashzadeh, et al 2019). Na atuação desta ou de outras ações, os profissionais evitam atuar sozinhos, pois ter um colega junto ajuda em situações violentas e também muitos contam com os colegas em situações de conflitos quando não estão bem, ou até mesmo buscam uma conversa após o ocorrido (Rajabi, Jahangiri, Bagherifard, Banaee & Fahadi, 2020). Em outra pesquisa (Zhao, et al 2016), os profissionais Research, Society and Development, v. 9, n. 11, e2279119780, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9780 preferiram a ajuda de um colega diante de situações de violência.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Manter o senso de humor e até confrontar o agressor são mecanismos individuais que também aparecem nos estudos (Abraham, 2018;Dadashzadeh, et al 2019). Na atuação desta ou de outras ações, os profissionais evitam atuar sozinhos, pois ter um colega junto ajuda em situações violentas e também muitos contam com os colegas em situações de conflitos quando não estão bem, ou até mesmo buscam uma conversa após o ocorrido (Rajabi, Jahangiri, Bagherifard, Banaee & Fahadi, 2020). Em outra pesquisa (Zhao, et al 2016), os profissionais Research, Society and Development, v. 9, n. 11, e2279119780, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9780 preferiram a ajuda de um colega diante de situações de violência.…”
Section: Discussionunclassified
“…Estudos apontam para a necessidade de reforços na segurança como patrulhas e policiais estacionados em frente aos locais de trabalho, bem como medidas de segurança como a instalação de câmeras, de botões de pânico ou alarmes pessoais (Rajabi, et al 2020;Zhao, et al 2016). D'ettorre e colaboradores (2018) expõem que os profissionais precisam melhorar suas habilidades de comunicação e promovê-la.…”
Section: Discussionunclassified
“…Triangular fuzzy set The operation rules in Reference [108] Trapezoidal fuzzy set The operation rule in Reference [100] Gray set The operation rules in Reference [109] Intuitionistic fuzzy set The operation rules in Reference [90] Interval-valued triangular fuzzy set The operation rules in Reference [110] Interval-valued Intuitionistic fuzzy set The operation rules in Reference [111] Interval-valued Pythagorean fuzzy set The operation rules in Reference [112] Hesitant fuzzy linguistic term set The operation rules in Reference [113] Interval type-2 hesitant fuzzy set The operation rules in Reference [114] Rough set The operation rules in Reference [115] Probability multivalued neutrosophic set The operation rules in Reference [116] Z-number The operation rules in Reference [117] Picture fuzzy set The operation rules in Reference [118] information, some researchers converted the linguistic variables to triangular fuzzy number 23,27,29,31,34,41,43,46,48,50,51,60,70,72,76,80,82,84 some converted linguistic variables to gray numbers, 42,58,104 some converted the linguistic variables to rough numbers. 106 In addition, combining with the situation that experts are usually hesitant when giving their evaluations, Liao et al 8 extended the ARAS method to hesitant fuzzy linguistic environment and proposed a BWM-ARAS framework for finance supplier selection in digital supply chain, in which they used the operation rules for hesitan...…”
Section: Information Forms Operation Rulesmentioning
confidence: 99%
“…23 In addition, there are also some researchers that focused on the evaluation of strategies for controlling violence against healthcare workers. 51 Nikabadi and Zamani 49 ranked the influencing factors of supply chain strategic outsourcing of small-and medium-sized manufacturing enterprises through the ARAS method, and found that the "quality" had the deepest influence for the outsourcing.…”
Section: Studies About Strategy Managementmentioning
confidence: 99%
“…Finally, he used the ARAS-F method to give priority to control measures of workplace violence. His method is not practical [8]. Gaber et al's research attempts to overcome the lack of reliable estimation of Malaysian users' willingness to pay for public transport (especially buses) through a fuzzy analytic hierarchy process (FAHP) [9].…”
Section: Introductionmentioning
confidence: 99%